Integrating and Evaluating Interdisciplinary Sustainability and STEM Curriculum in Geographical Education: A Case of Three Teaching Modalities. Issue 2 (4th March 2022) - Gilbertz, Susan; Wood, Brittany; Craig, Christopher; Karabas, Ismail; Petrun Sayers, Elizabeth; McCormick, Benjamin
Abstract: The effectiveness of interdisciplinary sustainability curriculum remains understudied in geography education. Accordingly, we deployed and evaluated an interdisciplinary sustainability and STEM module for in-person and online sections of a fall 2018 Human Geography course. Results indicate that sustainability knowledge improved after the interdisciplinary curricular intervention irrespective of course modality. Another focus is to explore student reactions to teaching modality due to COVID-19 disruptions. Results indicate that online student sustainability knowledge also improved during COVID-19 (fall 2020). For students in a section converted from in-person to blended, sustainability knowledge did not improve. Implications are provided.